The risks of healthcare-associated infections in healthcare settings of the Rostov region - S. A. Nenadskaya; E. V. Kovalev; E. G. Erganova; N. V. Leonenko; O. A. Noskova; V. V. Batashev; S. Yu. Vodyanitskaya; I. K. Dorofeeva; A. S. Chernaya; A. A. Voloshka (Медицинский вестник Юга России, 2024)
Objective: to analyze the incidence of healthcare-associated infections (HAIs) in healthcare settings of the Rostov region and the risks of their occurrence in order to develop proposals for improving the complex of anti-epidemic and preventive measures to prevent HAIs in healthcare settings of the Rostov region at present.Materials and methods: the materials for the work were data from reports "On the state of sanitary and epidemiological welfare of the population in the Rostov region" during 2009–2022, inspection reports and instructions from officials of the Department of Rospotrebnadzor in the Rostov region, expert opinions of specialists from the filial of the Federal Budgetary Healthcare Institution "Center for Hygiene and Epidemiology in the Rostov Region" in Rostov-on-Don on selective inspection of healthcare setting in 2021-2023. The work used an operative and retrospective epidemiological analysis.Results: the results of the analysis of the incidence of HAIs and the risks of their occurrence in healthcare settings of the Rostov region distinctly demonstrated the relevance of the problem of HAIs. To ensure the safety of medical care in the Rostov region, additional professional training programs about prevention of HAIs have been developed for medical workers.Conclusion: the results obtained made it possible to identify the risks of HAIs and propose specific measures to improve the complex of anti-epidemic and preventive measures to prevent HAIs in healthcare settings of the Rostov region.